Assessing genetic divergence in seedling trees of Persian walnut (Juglans regia) - SHARMA, O C; MURKUTE, A A; KANWAR, M S (The Indian Journal of Agricultural Sciences, 2010)
A study was conducted during 2006 and 2007 at KVK Leh (Ladakh), J&K to assess the nature and magnitude of genetic divergence of 216 bearing trees of Persian (Juglans regia L.)walnut of seedling origin growing at various ecogeographical regions in the cold arid region of India were subjected to non-hierarchical Euclidean cluster analysis based on 13 nut and kernel characters. Minimum and maximum values of co-efficients of variability were recorded for nut width and kernel weight, respectively. All 216 walnut gentotypes were grouped into 10 clusters. The clustering pattern of walnut genotypes belonging to the same eco-geographical region revealed their distribution in more than one cluster showing non-parallelism between geographic and genetic diversity. The first component presented maximum eigen root value and per cent variation. Maximum mean nut weight, kernel weight and kernel percentage was recorded in clusters 2, 2 and 6, respectively; while the average minimum shell thickness was found in cluster 6. The genotypes of cluster 2 and 9 were found highly diverse from each other and will give better segregants after hybridization which can then be used as cultivar in the future.